Effect of on-pump vs. off-pump coronary artery bypass grafting in patients with non-dialysis-dependent severe renal impairment: propensity-matched analysis from the UK registry dataset - Fudulu, Daniel P.; Argyriou, Amerikos; Kota, Rahul; Chan, Jeremy; Vohra, Hunaid; Caputo, Massimo; Zakkar, Mustafa; Angelini, Gianni D. (Frontiers in Cardiovascular Medicine, 2024)
On-pump coronary artery bypass (ONCAB) in patients with a pre-existing poor renal reserve is known to carry significant morbidity and mortality. There is limited controversial evidence on the benefit of off-pump coronary artery bypass (OPCAB) in these high-risk groups of patients. We compared early clinical outcomes in propensity-matched cohorts of patients with non-dialysis dependant pre-operative severe renal impairment undergoing OPCAB vs. ONCAB, captured in a large national registry dataset.All data for patients with a preoperative creatinine clearance of less than 50 ml/min who underwent elective or urgent isolated OPCAB or ONCAB from 1996 to 2019 were extracted from the UK National Adult Cardiac Surgery Audit (NACSA) database. Propensity score matching was performed using 1:1 nearest neighbour matching without replacement using several baseline characteristics. We investigated the effect of ONCABG vs OPCABG in the matched cohort using cluster-robust standard error regression.We identified 8628 patients with severe renal impairment undergoing isolated CABG, of which 1142 (13.23 %) underwent OPCAB during the study period. We compared 1141 propensity-matched pairs of patients undergoing OPCAB vs. ONCAB. The median age of the matched population was 78 years in both groups, with no significant imbalance post-matching in the rest of the variables. There was no difference between OPCAB and ONCAB in in-hospital mortality rates, postoperative dialysis, stroke rates. However, the return to theatre for bleeding or tamponade was higher in ONCABG versus OPCAB (p>0.02); however, OPCAB reduced the total length of stay in the hospital by one day (P=0.008). After double adjusting in the matched population using cluster-robust standard regression, ONCAB did not increase mortality compared to OPCAB (OR 1.05, P=0.78), postoperative stroke (OR 1.7, P=0.12) and dialysis (OR 0.7, P=0.09); however, ONCABG was associated with increased risk of bleeding (OR 1.53, P=0.03).